2002
DOI: 10.1097/00000542-200211000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Two Different Genetic Traits in Malignant Hyperthermia Families

Abstract: Based on genetic and diagnostic test data, more than one MHS allele associated with the MHS phenotype was evidenced in four families. These data should be considered in view of the use of genetics for the diagnosis of MHS and when reaching conclusions of genetic heterogeneity in MHS families. Taking into account the usual dominant mode of transmission of MHS and the size of the investigated population, the authors propose an evaluation of the incidence of the MHS in the general population based on genetic data. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 180 publications
(39 citation statements)
references
References 25 publications
1
35
0
2
Order By: Relevance
“…Over 100 RyR1 mutations have been associated with MH, involving inappropriate activation of RyR1, which causes uncontrolled release of SR Ca 2+ and muscle contractions. MH occurs at a rate of 1:50,000–100,000 adults and 1:15,000 children undergoing anesthesia; some studies have suggested a much more frequent rate of 1:5000 adults with MH susceptible mutations occurring at 1:3000 (Rosenberg et al 2007; Monnier et al 2002). The exact prevalence of MH susceptibility is difficult to determine since the syndrome only becomes apparent after exposure to triggering agents including volatile anesthetic agents such as halothane, isoflurane, sevoflurane, desflurane, enflurane and the neuromuscular blocking agent succinylcholine (Larach 2007).…”
Section: Malignant Hyperthermia (Mh)mentioning
confidence: 99%
“…Over 100 RyR1 mutations have been associated with MH, involving inappropriate activation of RyR1, which causes uncontrolled release of SR Ca 2+ and muscle contractions. MH occurs at a rate of 1:50,000–100,000 adults and 1:15,000 children undergoing anesthesia; some studies have suggested a much more frequent rate of 1:5000 adults with MH susceptible mutations occurring at 1:3000 (Rosenberg et al 2007; Monnier et al 2002). The exact prevalence of MH susceptibility is difficult to determine since the syndrome only becomes apparent after exposure to triggering agents including volatile anesthetic agents such as halothane, isoflurane, sevoflurane, desflurane, enflurane and the neuromuscular blocking agent succinylcholine (Larach 2007).…”
Section: Malignant Hyperthermia (Mh)mentioning
confidence: 99%
“…The prevalence of genetic variants predisposing to MH has been estimated to be as high as 1:2,000 1,2 . In most families MH shows an autosomal dominant pattern of inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…The published prevalence of MHS mutations varies widely from 1 in 2,000 1,32 to 1/10,000 4 but the penetrance has been difficult to determine. Our study of 870 exomes, although it represents a prodigious amount of data, is still too small to estimate the prevalence of MHS.…”
Section: Discussionmentioning
confidence: 99%